A comprehensive review on sustainable clay-based geopolymers for wastewater treatment: circular economy and future outlook - Maged, Ali; El-Fattah, Hadeer Abd; Kamel, Rasha M.; Kharbish, Sherif; Elgarahy, Ahmed M. (Environmental monitoring and assessment, 2023)
In the present era of significant industrial development, the presence and dispersal of countless water contaminants in water bodies worldwide have rendered them unsuitable for various forms of life. Recently, the awareness of environmental sustainability for wastewater treatment has increased rapidly in quest of meeting the global water demand. Despite numerous conventional adsorbents on deck, exploring low-cost and efficient adsorbents is interesting. Clays and clays-based geopolymers are intensively used as natural, alternative, and promising adsorbents to meet the goals for combating climate change and providing low carbon, heat, and power. In this narrative work, the present review highlights the persistence of some inorganic/organic water pollutants in aquatic bodies. Moreover, it comprehensively summarizes the advancement in the strategies associated with synthesizing clays and their based geopolymers, characterization techniques, and applications in water treatment. Furthermore, the critical challenges, opportunities, and future prospective regarding the circular economy are additionally outlined. This review expounded on the ongoing research studies for leveraging these eco-friendly materials to address water decontamination. The adsorption mechanisms of clays-based geopolymers are successfully presented. Therefore, the present review is believed to deepen insights into wastewater treatment using clays and clays-based geopolymers as a groundbreaking aspect in accord with the waste-to-wealth concept toward broader sustainable development goals.